Longitudinal evaluation of motor function in patients who underwent prenatal or postnatal neural tube defect repair. (13th July 2021) - Corroenne, R.; Yepez, M.; Pyarali, M.; Fox, K.; Mastrobattista, J. M.; Mack, L. M.; Lee, W.; Whitehead, W. E.; Castillo, H. A.; Castillo, J.; Mehollin‐Ray, A. R.; Espinoza, J.; et al.
ABSTRACT: Objective: To compare the evolution of motor function from mid‐gestation to 12 months of age between prenatally and postnatally repaired cases of open neural tube defect (ONTD). Methods: This was a retrospective cohort study of all fetuses that underwent prenatal (fetoscopic or open hysterotomy) or postnatal ONTD repair at a single institution between November 2011 and December 2018. The anatomical level of the lesion was defined as the upper bony spinal defect at initial magnetic resonance imaging assessment. Prenatal motor function of the lower extremities was evaluated by ultrasound according to the metameric level of the neurological lesion, based on the methodology of Carreras et al. Fetal motor function was assessed at referral, at 6 weeks after surgery in prenatally repaired cases or 6 weeks after referral in postnatally repaired cases (6‐week follow‐up) and at the last scan before delivery. In addition, motor function was assessed by a detailed neurological examination at birth and 12 months of age. First sacral (S1) neurological level of the lesion was considered as intact motor function. For statistical comparisons, we attributed numerical scores to each neurological level and motor function was expressed as median (range) neurological level. Motor function (as numerical score) and the proportion of cases with intact motor function and with motor function two or more levels better than expected based on the anatomical level of the lesion were compared between the prenatal‐ and postnatal‐repair groups. Fetal motor function was compared to the anatomical level of the lesion at referral and a better motor function was defined when it was two or more levels better than the anatomical level of the lesion. To assess the evolution of motor function, we compared motor function at referral with that at each follow‐up assessment using paired t ‐tests. Results: We included 127 patients with ONTD, of whom 93 underwent prenatal (51 fetoscopic and 42 open hysterotomy) and 34 postnatal repair. At the time of referral, cases in the prenatal‐ and postnatal‐repair groups presented with a similar anatomical level of lesion (L3 (T9–S1) vs L3 (T7–S1); P  = 0.52), similar motor function (S1 (L1–S1) vs S1 (L1–S1); P  = 0.52) and a similar proportion of cases with intact motor function (81% vs 79%; P  = 0.88) and with motor function two or more levels better than expected based on the anatomical level of the lesion (62% vs 74%; P  = 0.24). When compared with prenatally repaired cases, postnatally repaired cases showed worse motor function at birth (S1 (L1–S1) vs L4 (L1–S1); P  < 0.01) and at 12 months of age (S1 (L1–S1) vs L4 (L1–S1); P  < 0.01). In the prenatal‐repair group, motor function remained stable from the time of referral to 12 months of age ( P  = 0.26). Furthermore, the proportion of patients with intact motor function at referral (81% (75/93)) was similar to that at the 6‐week follow‐up (74% (64/87)), at the last scan before birth (74% (42/57)), at birth (68% (63/93)) and at 12 months of age (67% (39/58)) in the prenatal‐repair group. In the postnatal‐repair group, worse motor function, starting from the third trimester to 12 months of age, was observed. The proportion of patients with intact motor function at referral (79% (27/34)) was similar to that at 6‐week follow‐up (80% (12/15); P  = 0.92), but was lower at the last assessment before birth (25% (2/8); P  < 0.01), at birth (24% (8/34); P  < 0.01) and at 12 months of age (28% (7/25); P  < 0.01). Similar findings were noted when assessing the evolution of the proportion of cases with motor function two or more levels better than expected based on the anatomical level of the lesion in each group. Conclusions: Infants with ONTD that underwent postnatal repair had worse motor function at birth and at 12 months of age than at mid‐gestation and when compared with infants that underwent prenatal ONTD repair. Prenatal motor function assessment by ultrasound is an adequate tool to identify those infants who should have a good clinical motor function after delivery. Information obtained by fetal motor function assessment can have an important role for patient counseling and case selection for surgery. © 2020 International Society of Ultrasound in Obstetrics and Gynecology